Determining Qualification Level of Business Processes of an Organization Working in Ready Made Garment Sector - Şahan Vahaplar, Senem; Şen, Ali (My University, 2008)
This paper presents a case study of Harrington qualification criteria in ready-made garment sector with the aim of improving the process by using the cause and effect relationship between process qualification and process performance. Harrington criteria qualifies business processes in one of six levels, examining whether they satisfy the requirements determined for eight change areas; end-customer related measurements, process measurements and/or performance, supplier partnerships, documentation, training, benchmarking, process adaptability and continuous improvement. As a result of the case study, the process, which was qualified at level 6 at the beginning of the improvement studies, is upgraded to level 5. Copyright of Journal of Textile & Apparel / Tekstil ve Konfeksiyon is the property of Tekstil ve Konfeksiyon and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract.

Bu çalışmada, konfeksiyon sektöründe Harrington kriterlerinin uygulanması üzerine bir alan çalışması sunulmaktadır. Çalışmanın amacı; süreç niteliği ve süreç performansı arasındaki sebep-sonuç ilişkisini kullanarak tekstil iş sürecinde iyileşme sağlamaktır. Harrington kriterleri iş süreçlerini altı seviyede sınıflandırır. Bu sınıflandırmayı yaparken sürecin, sekiz değişim alanı için belirlenmiş gereklilikleri sağlayıp sağlamadığına bakar. Sekiz değişim alanı; son müşteri ile ilgili ölçümler, süreç ölçümleri ve/veya performansı, tedarikçi ilişkileri, dokümantasyon, eğitim, kıyaslama, süreç adaptasyonu ve sürekli gelişimdir. Yapılan alan çalışmasının sonucunda; süreç iyileştirme çalışmalarının başında 6. seviyede olan tekstil iş süreci 5. seviyeye yükseltilmiştir
Bir Konfeksiyon İşletmesinde İş Süreçlerinin Nitelik Seviyesinin Belirlenmesi
Keywords: Process performance criteria; Performance measurement; Harrington qualification criteria; Ready-made garment sector; Textile business process; Süreç performans kriterleri; Performans ölçümü; Harrington nitelendirme kriterleri; Konfeksiyon sektörü; Tekstil iş süreci